ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP ENTERPRISE VALUE dengan EARNING MANAGEMENT SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada Perusahaan BUMN yang Terdaftar pada Bursa Efek Indonesia (BEI) tahun 2006 - 2011) - Theda Margary Velda; Tarmizi Achmad (Diponegoro Journal of Accounting, 2013)
This research aimed to empirically examine the effect of corporate social responsibility disclosure to enterprise value and earnings management role as a moderating variable in the relationship between corporate social responsibility disclosure and enterprise value. Mechanism of earnings management using discretionary accruals are measured using the model of De Angelo (1986) and developed by Friendlan (1994). Corporate social responsibility disclosure in corporate social measure using disclosure index (CSDI) based on standard items reporting Global Reporting Initiative (GRI) are disclosed in the company's annual report. Enterprise value measurements using Tobin-Q value is based on the company's stock price.This research used samples on state-owned enterprises listed on the Stock Exchange during the years 2007-2011 by using purposive sampling Method. The data used were obtained from the annual report and sustainability report state-owned company listed on the Stock Exchange. There are 14 companies and 60 observations during the years 2007 to 2011 which fulfilling. The method of analysis used in this research is multiple regression analysis. This method was chosen because all the data is matrix data of variables.This research found significant statistically results from the influence of corporate social responsibility disclosure to the enterprise value. The research found no significant effect of earnings management on the relationship between corporate social responsibility disclosure by enterprise value. This study contributes to the literature providing shows that the amount of enterprise value influenced how many corporate social responsibility disclosures made by the company. However, in this research found that earnings management is carried out by the management cannot be effected to the extent of disclosure made by the company.